2018
DOI: 10.1080/1744666x.2018.1440205
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation in anti-neutrophil cytoplasmic antibody vasculitis

Abstract: Anti-neutrophil cytoplasmic antibody-associated vasculitis (AAV) has the propensity to acquire a devastating disease course. Despite the advances in therapeutics, a significant proportion of patients progress to end-stage renal disease (ESRD). Renal transplantation is being increasingly employed in this population, with gradual improvement in outcomes over the years, however, recurrence of disease requires constant surveillance and is associated with graft failure. Areas covered: A structured literature search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Because the effect of MMF in preventing rejection of transplanted kidneys has also been established, MMF is recommended unless it is contraindicated or intolerable. 34 Because recurrence of AAV was not observed in this study, MMF would be recommended for use after RTx.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Because the effect of MMF in preventing rejection of transplanted kidneys has also been established, MMF is recommended unless it is contraindicated or intolerable. 34 Because recurrence of AAV was not observed in this study, MMF would be recommended for use after RTx.…”
Section: Discussionmentioning
confidence: 79%
“…However, after RTx, the recurrence rate in patients undergoing combination therapy with antibody induction, TAC, and MMF has been reported to be lower than that in non‐ESRD patients. Because the effect of MMF in preventing rejection of transplanted kidneys has also been established, MMF is recommended unless it is contraindicated or intolerable . Because recurrence of AAV was not observed in this study, MMF would be recommended for use after RTx.…”
Section: Discussionmentioning
confidence: 88%
“…One cohort study, in particular, demonstrated that patient and transplant survival was better in AAV compared to nondiabetic patients [45]. Various single and multi-center cohort studies have evaluated the outcomes of renal transplantation in patients with AAV [8,11,12,19,22,[46][47][48][49][50][51] and have shown that the rate of patient and transplant survival in AAV is equal and comparable to control nondiabetic patients. The five-year posttransplant patient survival ranges between 77% and 96%, and the five-year graft survival is between 60% and 100%.…”
Section: Outcomes Of Kidney Transplantation In Aavmentioning
confidence: 99%
“…In the case of a recurrence, the treatment options for remission induction are similar to those of nontransplanted patients. Both cyclophosphamide- and RTX- based induction regimens have shown effectiveness in the treatment of posttransplant relapses[182].…”
Section: Indications For Ta In Ktmentioning
confidence: 99%
“…TPE is recommended, in conjunction with glucocorticoids and either cyclophosphamide or RTX in the setting of relapse manifesting as alveolar hemorrhage, severe segmental necrotizing glomerulonephritis with serum creatinine above 4.0 mg/dL, and concurrent anti-GBM disease[182-184].…”
Section: Indications For Ta In Ktmentioning
confidence: 99%